A Development of Number Circuit Game Based Learning Strategy to Introduce Numeral Symbols for Children Aged 4-5 Years - Rahmi Wardah Ningsih; Slamet Suyanto; Fauzi Fahmi (STAI Auliaurrasyidin Tembilahan, 2021)
Understanding the concept of numeral symbols in early childhood is fundamental to understanding mathematical concepts in the future. In view of that, children aged 4-5 years found many problems such as unable to distinguish the form of number symbols, unappropriated learning strategies, and monotonous learning activities. This study aimed to: (1) develop the learning strategies using number circuit games to introduce numeral symbols for 4-5-year-old-children; (2) assess the effectiveness of implementing number circuit games as the learning strategies introducing numeral symbols for 4-5-year-old children. ADDIE with five stages – namely analysis, design, development, implementation, and evaluation – was adopted in this research. The data were analyzed descriptively through qualitative and quantitative techniques. The evidence revealed that: (1) the introduction of numeral symbols for 4-5-year-old children by memorizing and understandings required the implementation of game-based learning strategies; (2) number circuit games which were modified based on the material, the implementation, and the purpose were suitable for children of 4-5 years old; (3) learning strategies using number circuit games to introduce numeral symbols for children of 4-5 year with p-value. Sig 0.000 < 0.05 had revealed that there were significant differences in children’s ability in identifying the numeral symbols.